(untitled) (Journal of Economic Research & Business Administration, 2021)
The contribution of small and medium-sized businesses to the Kazakhstan’s GDP is just over 27%, and the share of innovative enterprises in this sector of the economy is just over 0.98%. Currently the share of SMEs in Japan’s GDP is 95 percent, the United States – 80%, Western Europe – 60%. In order to be more economically stronger and independent of oil bondage for national economy is advised to increase SMEs proportion. The primer goal of this publication to raise concerns and recommendations on boosting digital literacy within SMEs owners, particularly in agribusiness and government structures. It is undeniable that without interconnection or as they say government-private partnership such capital needed processes like digitalization of business processes for both public and private success would not be seen. The further development of digitalization in agriculture is hindered not by the availability or weak development of Internet connections, as well as the lack of local systems for spreading knowledge and training specialists in the use of digital tools. For various solutions in the process of the study appropriate qualitative research methods have been used: monographic, analysis and synthesis, logical and abstractive constructional, etc. In this paper ongoing digitalization processes from government of Kazakhstan in general was presented, application of this process to one of the most important industry (agriculture) is shown, problems for further advancement of digitalization of economy is pointed and some developments were made. The object of research is the processes and tools of digitalization of decision-making used by small and medium-sized agribusiness in Kazakhstan. The findings of this study contribute to preparation and advancing of conceptual development of digitalization for business-government relationships, therefore increasing competitiveness of industry and economy intact. Key words: digitalization, new technologies, digital solutions, small and medium business, IT solutions, IT platforms.